Perlindungan Hukum Terhadap Pasien Dalam Pelayanan Medis Di Rumah Sakit Umum - Marsri Tulak Randabunga Sidabuke (Lembaga Pengembangan Kinerja Dosen, 2023)
Medical services are the object of forgiveness for treatment and care. So efforts to improve people's living standards in the health sector, is a comprehensive necessity including improving public health physically and non-physically. In this case, the patient is someone who receives medical treatment. The patient's right as a recipient of medical services is to obtain information on medical services to find out the results of the examination/diagnosis that has been carried out by the medical team and the right to know what action the patient must receive.